POLIGAMI PERSFEKTIF ISLAM DAN UNDANG-UNDANGAN PERKAWINAN DI INDONESIA - Djaenab Djaenab (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2020)
This article outlines Islamic Perspective Polygamy and Marriage Legislation in Indonesia. From the results of the discussion obtained an understanding that, the origin of polygamy law in marriage according to Islam and marriage legislation in Indonesia is monogamy, because with monogamy will neutralize the nature and character of jealousy, jealousy that exists in every wife. These properties will appear with high levels if polygamy practices occur, so that it can disturb the calm and endanger the integrity of the family. The ability of polygamy can only be done in an emergency and with strict conditions.